2018
DOI: 10.1002/mds.27362
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MDS clinical diagnostic criteria for Parkinson's disease

Abstract: The International Parkinson and Movement Disorder Society criteria demonstrated high sensitivity and specificity compared with the gold standard, expert diagnosis, with sensitivity and specificity both higher than United Kingdom Brain Bank criteria. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
105
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(125 citation statements)
references
References 17 publications
3
105
0
5
Order By: Relevance
“…This is consistent with age being the greatest risk factor for Parkinson's disease and the idea that Parkinson's is a disease of accelerated ageing (83). Finally, there is a need for a Parkinson's biomarker (84,85). Measuring translation from peripheral cells could potentially lead to a biomarker readout.…”
Section: Discussionsupporting
confidence: 58%
“…This is consistent with age being the greatest risk factor for Parkinson's disease and the idea that Parkinson's is a disease of accelerated ageing (83). Finally, there is a need for a Parkinson's biomarker (84,85). Measuring translation from peripheral cells could potentially lead to a biomarker readout.…”
Section: Discussionsupporting
confidence: 58%
“…Overall, the MDS‐PSP criteria perform very favorably compared with other criteria for clinical diagnosis of other neurodegenerative disorders. For comparison, a recent study of the PD criteria found an 11.5% false‐positive rate, sensitivity of 94.5%, and specificity of 88.5% . Sensitivity of the clinical diagnosis of Alzheimer's disease (AD) ranges from 70.9% to 87.3% and specificity from 44.3% to 70.8% .…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, a recent study of the PD criteria found an 11.5% false-positive rate, sensitivity of 94.5%, and specificity of 88.5%. 24 Sensitivity of the clinical diagnosis of Alzheimer's disease (AD) ranges from 70.9% to 87.3% and specificity from 44.3% to 70.8%. 25 Similarly, criteria for "possible bvFTD" have sensitivity of 95% and specificity of 82%, whereas "probable bvFTD" has a sensitivity of 85% and specificity of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…who had more than 10 years of experience in the diagnosis of movement disorders. Although new clinical diagnostic criteria for PD have been recently proposed 43 and very recently validated, 44 these criteria have not been used in our patients because the patient recruitment ended before the publication of the new diagnostic criteria. Second, the abnormalities of vertical saccades may occasionally be present both in aging and in vascular parkinsonism.…”
Section: Discussionmentioning
confidence: 99%